Analisis Kebijakan Kuota 30% Keterwakilan Perempuan dalam Politik Indonesia - Keisya Damayanti; Caritas Nadya Anisti; Reivania Calista Rizanul; Aniqotul Ummah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This research examines the implementation of the 30% women's representation quota policy in Indonesian politics. Using a qualitative method with a descriptive analytical approach through library research, this study analyzes the challenges and effectiveness of affirmative action policies for women in politics. The findings show that despite the quota policy, women's representation in legislative bodies remains inadequate due to several factors, including patriarchal culture, limited access to political education, and varying levels of political party commitment. The study reveals that patriarchal social systems tend to position men in higher public roles while women are expected to focus on domestic roles, leading to detrimental stereotypes that reduce women's interest and confidence in political participation. Additionally, women face internal challenges such as limited political experience and knowledge due to restricted access to political education and training. Political parties' varying commitment to affirmative policies further compounds these challenges, with some parties merely fulfilling the 30% quota as an administrative requirement. This study recommends comprehensive measures including enhanced political education for women, gender equality awareness programs, strengthened support from political parties, and systemic changes in social and political structures to achieve more effective women's representation in Indonesian politics.